Characterizing surface properties of oxidized coal using FTIR and contact angle measurements. Issue 12 (18th June 2018) - Zhou, You; Albijanic, Boris; Wang, Yuling; Yang, Jianguo
ABSTRACT: This paper compares FTIR (Fourier Transform Infrared Spectroscopy) and contact angle measurements to characterize surface properties of the oxidized coals with different ash contents. FTIR analysis was employed to investigate functional chemical groups of the oxidized coals. Contact angle measurements were utilized to characterize the hydrophilicity of the oxidized coal. The results showed that contact angle measurements were the same regarding of the type of the oxidized coal. However, FTIR results show that the coal samples with lower ash content had more hydrophobic groups and less hydrophilic groups than the coal samples with higher ash content. This paper demonstrated that FTIR technique is more sensitive than contact angle measurements in studying surface properties of oxidized coal samples.